Corporate Responses to Shareholder Activists: Considering the Dialogue Alternative - Rehbein, Kathleen; Logsdon, Jeanne M.; Van Buren, Harry J. (2013)
This empirical study examines corporate responses to activist shareholder groups filing social-policy shareholder resolutions. Using resource dependency theory as our conceptual framing, we identify some of the drivers of corporate responses to shareholder activists. This study departs from previous studies by including a fourth possible corporate response, engaging in dialogue. Dialogue, an alternative to shareholder resolutions filed by activists, is a process in which corporations and activist shareholder groups mutually agree to engage in ongoing negotiations to deal with social issues. Based on a unique dataset of resolutions filed by member organizations of the Interfaith Center on Corporate Responsibility from 2002 to 2005 and the outcomes of these resolutions, our analysis finds that corporate managers are more likely to engage in dialogue with shareholder activists when the firm is larger, is more responsive to stakeholders, the CEO is the board chair, and the firm has a relatively lower percentage of institutional investors.
Keywords: Interfaith Center on Corporate Responsibility; social activism; shareholder resolutions; shareholder activism; Dialogue; Corporate Social Responsibility; Corporate Governance